1964
DOI: 10.1002/app.1964.070080604
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of free radical initiators with self‐extinguishing additives in vinyl aromatic polymers

Abstract: SynopsisVinyl aromatic polymers such as polystyrene can be made nonflammable by the addition of halogen compounds. The amount of halogen required to make such polymers nonflammable can now be greatly reduced by the addition of small amounts of certain free radical initiators. Normally about 5 phr of acetylene tetrabromide (parts of additive per hundred parts of polymer) must be added to polystyrene to obtain a self-extinguishing polymer. Only 0.5 phr of acetylene tetrabromide is required if 0.5 phr dicurnyl pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 26 publications
(5 reference statements)
1
19
0
Order By: Relevance
“…He proposed that the radical precursors trigger the decomposition of the halogenated flame retardant whereby halogen radicals are rapidly liberated that effectively interrupt the combustion process. [16] It is worth noting that all of the used radical precursors have very limited thermal stabilities and no indication has been given that they will exhibit flame retardancy properties on their own. In contrast, our studies have clearly demonstrated that alkyl radicals generated by the diazene radical precursors have the ability to effectively interrupt the combustion process at the right point by themselves.…”
Section: Resultsmentioning
confidence: 99%
“…He proposed that the radical precursors trigger the decomposition of the halogenated flame retardant whereby halogen radicals are rapidly liberated that effectively interrupt the combustion process. [16] It is worth noting that all of the used radical precursors have very limited thermal stabilities and no indication has been given that they will exhibit flame retardancy properties on their own. In contrast, our studies have clearly demonstrated that alkyl radicals generated by the diazene radical precursors have the ability to effectively interrupt the combustion process at the right point by themselves.…”
Section: Resultsmentioning
confidence: 99%
“…Thus it appears that at least part of the synergism associated with this system derives from the ability of Sb203 to moderate the release of halogen to the gas phase and over a considerable temperature range. This effect has a parallel in the use of substrate free radical initiators, such as dicumyl peroxide [34], which are believed to delay the Joss of haloge, n from the decomposing polymer.…”
Section: 1_ the Antimony Oxide-halogen Examplementioning
confidence: 99%
“…From the viewpoint of flame retardancy of polymers mainly radical generators triggered by thermolysis or redox systems have been successfully used to suppress and retard the fire response of polymeric materials [21,22]. In the past it has been demonstrated that certain peroxides can be used as synergists to enhance the action of brominated flame retardants (BFR) [23][24][25][26][27][28][29], whereas azo compounds [30] and alkoxyamines [12,31] have been shown to provide self-extinguishing properties to polymers even by themselves. Thus, it has been established that radical precursors that are capable of generating various carbon (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example some disulfides presented in this paper (e.g. disulfide 6) are claimed to be effective flame retardant synergists with halogens in polystyrene [23]. Moreover, elemental sulfur and other polysulfides are also known as effective flame retardant components [41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%